The Practicality of Popular Scientific Books based on the Diversity of Tree Species on the Puting Riverbank - Kristina Febriana Panjaitan; Muhammad Zaini; Danang Biyatmoko (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Learning resources using popular scientific books based on local potential found in an area is one solution that can be used to overcome problems in learning Plant Ecology courses. This development research aims to describe the practicality of the contents, expectations and actual prototypes of a popular scientific book entitled “Tree Species Diversity in Puting Riverbank”. The research method uses a Tessmer design that focuses on formative evaluation. The results of the research on the practicality test of the content seen from the readability results of students got an average value of 94.23% with very good criteria, while the results of the practicality test of expectations and actual seen from the results of the implementation of popular scientific books which obtained an average value of 88.89% with very good criteria and the results of student responses to popular scientific books with an average of 95.96% with criteria strongly agree. This shows that a popular scientific book with the title